The Migration Trajectories of Poles and Jews from Rzeszów to the United States at the Turn of the 20th Century – Shared or Divergent Routes? - Kulpińska, Joanna; Mitka, Przemysław; Tutko, Aleksandra; Dural, Julia (Migrations in the Slavic Cultural Space. From the Middle Ages to the Present Day, 2022)
The aim of the paper is to compare the migration streams of Poles and Jews from Rzeszów to the United States at the turn of the 20th century. The article is part of a project carried out within the framework of the Jagiellonian University’s Program of Excellence – POB Heritage, whose main goal is to indicate the specificity of emigration from urban communities at the beginning of the 20th century on the example of Rzeszów. The analysis was conducted in a comparative perspective both on the synchronic level, comparing the structure and mechanisms of migration of different ethnic groups living in Rzeszów at the turn of the 19th and 20th centuries, and at the diachronic level, reconstructing the migration time trends of the city’s inhabitants. The Polish and Jewish migration routes were compared in terms of socio-demographic data, structure of migration networks, and adaptation strategies in the host country. The presented analysis is based on the data from the Ellis Island Archive’s ship passenger lists. Information was collected on over 1500 immigrants who arrived from Rzeszów to the United States between 1884 and 1924.